Avaliação de peptídeo natriurético em cães doentes renais crônicos - Cruz, Felipe Augusto Constantino Seabra da (2016)
Hypertension is one of the most common complications of chronic kidney disease (CKD). Myocytes release natriuretic peptides and studies show increased concentration of peptides in hypertensive animals to compare them with healthy animals. This study aimed to evaluate patients with chronic kidney disease through blood count, urea, creatinine, urinalysis, creatinine ratio and urinary protein (UPC), blood pressure, measurement of electrolytes, electrocardiogram and natriuretic B peptide (BNP) in order to define its predictive value in different stages of CKD. It has been found significant differences in the UPC doses (p = 0.006), anemia, creatinine and BUN (p <0.001). Despite the variations in blood pressure, amplitude and QRS interval and phosphorus are not significant, it was observed changing trend of these values with the advance of the disease. There was no correlation between BNP and CKD.